Potensi Pendekatan in Silico Sebagai Penghambat Aktivitas Protein Protease Utama SARS-CoV-2 dari Tiga Senyawa Tanaman Obat Jahe Merah - Cut Annisa Thahara; Rizarullah Rizarullah*; Ratih Ayu Atika; Abdul Wahab (JIPI (Jurnal IPA dan Pembelajaran IPA), 2022)
Corona Virus Disease (COVID-19) is a pneumonia outbreak that has been worldwide to date. This outbreak was caused by a Coronavirus originating from Hubei province that first occurred in Wuhan in December 2019. COVID-19 is caused by SARS-CoV-2. SARS-CoV-2 which causes corona has important proteins that are used to infect and replicate, one of which is the main protease protein (Mpro). Red ginger (Zingiber officinale var.Rubrum) is one of the spices that has properties to cure various diseases such as flu, cough and diarrhea. Ginger contains compounds that are antioxidants. The purpose of this study was to examine the potential biological activity of red ginger compounds, namely Gingerol 10, Shogaol 6, and Shogaol 8 as inhibitors of the main protease (MPro) protein activity of SARS-CoV-2. This research was conducted using the In Silico method and AutoDock Vina software was used for the tethering process. The results of gridbox optimization by redocking control ligands obtained RMSD results of 1,100 Å. The results of the tethering showed Gibbs free energy (ΔG) Test Ligand 1 (-5.5 kcal/mol), Test Ligand 2 (-6.0 kcal/mol), and Test Ligand 3 (-5.6 kcal/mol) which showed red ginger compounds have potential as inhibitor of the main protease (MPro) protein activity of SARS-CoV-2.